2021
DOI: 10.1186/s40163-021-00141-0
|View full text |Cite
|
Sign up to set email alerts
|

Policing and public health calls for service in Philadelphia

Abstract: This contribution outlines various spatial and temporal aspects of medical or public-health related calls for service from the public to police in Philadelphia in 2019. These incidents comprise about 8% of the police department’s workload that originates from the public. Calls appear to be highly concentrated in a few areas, and specifically the Center City and Kensington neighborhoods. They are also more likely to occur late afternoon and evening. The article shows that some medical or public health activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Accordingly, we might have missed a small number of DV incidents as we constructed our time‐series data set. Some false positives may have also found their way into our data, as prior work demonstrates that many 911 calls are ultimately unfounded or determined upon officer arrival to be a problem other than what was originally reported (Ratcliffe, 2021 ; Sorenson, 2017 ). This just underscores the importance of seeking out alternative sources of data on DV help‐seeking, like the emergency hotline data analyzed here (see also Sorenson et al., 2021 ).…”
Section: Discussionmentioning
confidence: 79%
“…Accordingly, we might have missed a small number of DV incidents as we constructed our time‐series data set. Some false positives may have also found their way into our data, as prior work demonstrates that many 911 calls are ultimately unfounded or determined upon officer arrival to be a problem other than what was originally reported (Ratcliffe, 2021 ; Sorenson, 2017 ). This just underscores the importance of seeking out alternative sources of data on DV help‐seeking, like the emergency hotline data analyzed here (see also Sorenson et al., 2021 ).…”
Section: Discussionmentioning
confidence: 79%
“…Doing so can possibly mitigate or eliminate the need for police involvement later on, as was the case here. If a response is required, however, and in-light of increasing calls for civilian-based responses (Watson et al, 2021 ), recent research warns us that calls for service which are initially reported as involving PwPMI may in fact encompass other components that would require a police response (Lum et al, 2021 ; Ratcliffe, 2021 ). Future work is therefore needed as to how the police can safely and appropriately triage PwPMI calls with their local mental health partners, and particularly so during public health emergencies which can lead to an increase in such calls.…”
Section: Discussionmentioning
confidence: 99%
“…Despite what is portrayed in movies and on television, these 911 calls are rarely for serious violent crimes in progress (Ratcliffe, 2016(Ratcliffe, , 2021. 3 For calls that are serious, many are for crimes that have already occurred and in which the perpetrator is gone (Spelman & Brown, 1981).…”
mentioning
confidence: 99%